1993
DOI: 10.1080/15287399309531733
|View full text |Cite
|
Sign up to set email alerts
|

A multiyear study of blood cholinesterase activity in urban pesticide applicators

Abstract: This article is a review of blood cholinesterase activity in a cohort of urban pesticide applicators ranging from 1680 to over 3800 workers. During the period 1981-1991, 208, 788 blood samples were taken for measurement of cholinesterase activity with an average of 6 samples per year from each worker. A total of 150 workers or 0.44% of the cohort was removed from exposure to cholinesterase-inhibiting insecticides because of decreased cholinesterase activity. No worker required treatment for signs of cholineste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Nevertheless, this difference could be attributed to the fact that in the March-April period higher exposure to pesticides produced a reduction in the concentration of PChE. In this context it should be noted that several pesticides, such as organophosphates and carbamates (most used by these workers), are reported to be the major cause of a depression of serum cholinesterases (Yeary et al, 1993) and, as consequence, this is used as a good biomarker of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this difference could be attributed to the fact that in the March-April period higher exposure to pesticides produced a reduction in the concentration of PChE. In this context it should be noted that several pesticides, such as organophosphates and carbamates (most used by these workers), are reported to be the major cause of a depression of serum cholinesterases (Yeary et al, 1993) and, as consequence, this is used as a good biomarker of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide dismutase (SOD) is a major zinc/copper enzyme responsible for the dismutation of superoxide radicals generated by the autooxidation of hemoglobin, whereas d-aminolevulinic acid dehydratase (ALAD), a sulfhydryl enzyme, is essential for the synthesis of hemoglobin. Exposure to organophosphates and carbamates is reported to be the major cause of the depression of cholinesterase (an enzyme that catalyzes the hydrolysis of choline) in the blood of farm workers, though certain liver conditions can also inhibit the enzyme (IARC 1991;Yearly et al 1993). Many chemicals and toxic metals are known to alter the activities of these important enzymes because of the vicinal sulfhydryl group that is essential for the activity of ALAD (Maines 1980), whereas the zinc and copper atoms in SOD can be easily displaced by toxic metals such as cadmium (Linder 1991;Friberg et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Following chronic exposures to OPs, RBC AChE activity can be depressed gradually to very low levels without clinical effects (Heath & Vale, 1992). An 11-yr study, conducted by ChemLawn Services Corporation from 1981 to 1991, reported that 150 of 33,717 urban pesticide applicators were removed from work when a 30% reduction in RBC AChE activity was found following exposure to ChE inhibiting insecticides (Yeary et al, 1993). However, no employee, with the exception of two suicide attempts, exhibited signs of toxicity or cholinergic effects.…”
mentioning
confidence: 98%